2021
DOI: 10.7759/cureus.16274
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Herpes Zoster in an Adult Patient Recovered From Symptomatic Reinfection of COVID-19

Abstract: In coronavirus disease 2019 (COVID-19) patients, various dermatological conditions have been observed. Varicella zoster virus (VZV) and herpes simplex virus must be ruled out before considering vesicular exanthems linked to COVID-19. The immunological status of the host has an impact on the natural history of herpes zoster (HZ). Age is a major risk factor for most of the cases of HZ. Reactivation of VZV can be triggered by iatrogenic immunosuppression or disease-related immunocompromised state or age-related i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…A total of 314 studies were identified. After applying the inclusion and exclusion criteria, 55 studies [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] of VZV manifestations in subjects with SARS-CoV-2 vaccinations or COVID-19 disease were deemed eligible for inclusion. A flow diagram of the selection of the studies is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 314 studies were identified. After applying the inclusion and exclusion criteria, 55 studies [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] of VZV manifestations in subjects with SARS-CoV-2 vaccinations or COVID-19 disease were deemed eligible for inclusion. A flow diagram of the selection of the studies is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 19 articles with three observational studies and 16 case reports or series were included in the review. 6,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Description of included studies Table 1 describes the main characteristics of three observational studies from the scoping review. Giavedoni et al conducted a retrospective analysis of COVID-19 skin lesions in order to characterize the clinical patterns of the lesions.…”
Section: Data Extraction and Definitionmentioning
confidence: 99%
“…7 A few cases of COVID-associated HZ were reported during the current pandemic which unlike to our case, none of them pose a diagnostic challenge. [8][9][10][11] The majority of these cases including ours belonged to the age group above 50 years. 9 However, most of those patients developed cutaneous lesions up to 1 week after the onset of COVID symptoms, [12][13][14] which was not congruent with the course of disease in our patient.…”
Section: Discussionmentioning
confidence: 71%
“…A few cases of COVID‐associated HZ were reported during the current pandemic which unlike to our case, none of them pose a diagnostic challenge. 8 , 9 , 10 , 11 …”
Section: Discussionmentioning
confidence: 99%